Method of stability analysis of automatic systems with logic control devices when exposed to parametric perturbations on the basis of the sensitivity functions - Yukhymchuk, M. S.; Osipenko, H. A. (Visnyk of Vinnytsia Politechnical Institute, 2015)
This paper proposes a method of stability analysis of automatic systems with logic control devices when exposed to parametric perturbations, which allows determining the stability boundary of systems in the space of increasing parameters. The admissible intervals of parameters of nonlinear elements where the stability of control systems doesn’t change were found through mathematical modeling.